Transient elevation of ST-segment due to pneumothorax and pneumopericardium - Brandão, Rodrigo Martins; Gonçalves, Amanda Cristina Maria Aparecida; Brandão, Renata Paula Martins; Oliveira, Lucas Fernandes de; Nogueira, Antonio Carlos; Kawabata, Vitor Sérgio (Autopsy and Case Reports, 2013)
ST-segment elevation, observed in the critically ill patients, almost always raises the suspicion of ischemic heart disease. However, nonischemic myocardial and non-myocardial problems in these patients may also lead to ST-segment elevation. Pneumothorax and pneumopericardium have been rarely reported as a cause of transient ST-segment elevation. The authors report the case of a patient admitted to the emergency care unit because of a respiratory failure requiring mechanical ventilatory support. As the patient showed signs of clinical deterioration, a pneumothorax was clinically diagnosed. Chest radiography after thorax drainage also disclosed a pneumopericardium. The 12-lead electrocardiogram recorded before the thoracic drainage revealed an ST-segment elevation, which normalized after the surgical procedure. Ischemic myocardial biomarkers were negative. The authors call attention to the right-sided pneumothorax associated with pneumopericardium as an unusual cause of ST-segment elevation.